2021
DOI: 10.26719/2021.27.4.344
|View full text |Cite
|
Sign up to set email alerts
|

Impact of household food insecurity on maternal mental health in Egypt

Abstract: Background: Food insecurity leads to disturbed eating patterns, hunger or poor nutrition and is strongly correlated with poor mental health. Aims: To determine the impact of household food insecurity on maternal mental health in a rural population in Egypt. Methods: This community-based cross-sectional study was conducted in Qulubba Village in Minia Governorate. We interviewed 497 mothers with at least one child, using the Household Food Insecurity Access Scale and Hopkins Symptom Check List-25. Results: Nearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Consistent with previous studies, a strong positive correlation was detected between household food insecurity and maternal depression. A cross sectional study that targeted 497 women found that depressive symptoms were more common in food insecure mothers and that household food insecurity is a significant predictor of distress in mothers (Mahfouz et al, 2021). This research results were also aligned with Pourmotabbed et al's 2020 systematic review and meta-analysis of 19 studies, that showed an increased risk of depression among maternal caregivers who happen to reside in food insecure households.…”
Section: Correlation Between Household Food Insecurity and Maternal M...supporting
confidence: 68%
See 1 more Smart Citation
“…Consistent with previous studies, a strong positive correlation was detected between household food insecurity and maternal depression. A cross sectional study that targeted 497 women found that depressive symptoms were more common in food insecure mothers and that household food insecurity is a significant predictor of distress in mothers (Mahfouz et al, 2021). This research results were also aligned with Pourmotabbed et al's 2020 systematic review and meta-analysis of 19 studies, that showed an increased risk of depression among maternal caregivers who happen to reside in food insecure households.…”
Section: Correlation Between Household Food Insecurity and Maternal M...supporting
confidence: 68%
“…Lastly, Hadley and Patil (2006) proposed that with females usually being the caretakers of the children, the occurrence of anxiety or depression may be related to child care practices as well.. Most recently, a cross sectional study examining the link between maternal mental health and HFI in Egypt, found that symptoms of anxiety and depression were more significantly pronounced among food insecure mothers, with severely food insecure ones 13 times more likely to suffer from mental distress compared to their food secure counterparts (Mahfouz, Mohammed, Alkilany, and Abdel Rahman, 2021). Whether mothers tending to their children's health and nutritional needs in Lebanon suffer from mental health disturbances such as depression is still in question.…”
Section: Household Food Insecurity and Mental Healthmentioning
confidence: 99%
“…The prevalence of food insecurity in pregnant women in Syria exceeded that observed in other national studies carried out with women in the region: a whopping 73% compared to 32% in Jordan, 48% in Iran, 50% in Lebanon, and 69.6% in Egypt. [11][12][13] [14] It is also important to highlight that food insecurity is categorized according to the Household Food Security Survey into low and very low security. Their prevalence is 30.4% and 42.6%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to women with low socioeconomic status may face difficulties to fulfill their needs and newborns during the postpartum period. Low socioeconomic status has been connected with a high rate of different mental health problems [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%